Gambaran Pengetahuan Ibu-Ibu PKK Tentang Jamu Temulawak Sebagai Anti Kanker Payudara - Restu Ayu Eka Pustika Dewi; Lusiana Cici Sabarani (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2023)
Cancer rates in Indonesia increase significantly every year. One of the cancers with a high death rate is breast cancer. Breast cancer itself generally attacks women and is one of the most common cancers that occur in Indonesia. Jamu is a herbal drink that is still popular with people in Indonesia. Temulawak contains xanthorrizol essential oil which is capable of treating various pathological conditions. Jamu temulawak can potentially inhibit Ymb-1, T47D, and MCF-7 breast cancer cells. The purpose of this study was to describe the level of knowledge of PKK mothers about Jamu Temulawak as anti-breast cancer. The research method used in this study was descriptive analysis with cross-sectional sampling techniques. It was found that there were 33 respondents consisting of PKK RT 05 RW 02 Lamper Krajan Village, Lamper Lor Village, South Semarang District. Data was obtained from filling out the questionnaire by respondents who then processed the data using SPSS. The results of the study showed that the level of knowledge about temulawak herbal medicine as anti-breast cancer was in the sufficient category, namely there were 22 people (66.7%). The respondents' knowledge level about the processing of temulawak herbal medicine is still relatively low, namely 17 people (51.5%). The majority of respondents obtained information from electronic media, there were 31 people (93.9%). The importance of increasing the knowledge of mothers about Jamu Temulawak as anti-breast cancer to prevent an increase in cases of death caused by breast cancer.